Does Escalating Violence and Associated Fear of Crime Worsen Psychological Well-Being in Community Dwellers Living in a Rural Setting? Results From the Atahualpa Project Cohort - Oscar H. Del Brutto; Robertino M. Mera; Denisse A. Rumbea; Emilio E. Arias; Mark J. Sedler (SAGE Publishing, 2024)
Background: Escalating street violence and criminal homicides have an adverse impact on psychological well-being. However, these consequences have been difficult to evaluate. Using a recently validated scale, we aimed to assess the impact of fear of crime on the psychological status of middle-aged and older adults living in a rural setting afflicted by endemic violence. Methods: Participants were selected from Atahualpa residents included in previous studies targeting psychological distress in the population. A validated scale was used to objectively quantify fear of crime in participants. Differences in symptoms of depression and anxiety between baseline and follow-up were used as distinct dependent variables and the continuous score of the fear of crime scale was used as the independent variable. Linear regression models were fitted to assess the association between the exposure and the outcomes, after adjusting for relevant confounders. Results: A total of 653 participants (mean age = 53.2 ± 11.5 years; 57% women) completed the requested tests. We found a 13% increase in symptoms of depression and anxiety during the peak of violence in the village compared with previous years. Linear regression models showed a significant association between the total score on the fear of crime questionnaire and worsening symptoms of depression (β = .24; 95% CI = 0.14-0.35) and anxiety (β = .31; 95% CI = 0.24-0.37), after adjustment for relevant confounders. Conclusions: This study shows a significant aggravating effect of fear of crime on pre-existing symptoms of depression and anxiety and a deleterious effect of these conditions on overall well-being.